2023
DOI: 10.1039/d3sm00368j
|View full text |Cite
|
Sign up to set email alerts
|

Transparent ionic conductive elastomers with high mechanical strength and strong tensile properties for strain sensors

Abstract: Stretchable ionic conductive elastomers have been extensively studied due to their great application potential in the fields of sensors, batteries, capacitors and flexible robots. However, it is still challenging to...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 59 publications
(77 reference statements)
0
3
0
Order By: Relevance
“…For the ICTE and C-PEG, the first-stage weight loss above 100 °C is likely related to the volatilization of residual water and PC . Although the initial weight loss temperature of the ICTE was 100 °C, the weight loss rate (<0.5%) was almost negligible in plastic processing. , In this study, the preparation and molding of the ICTE were conducted at 92 °C, indicating that the ICTE remained highly stable during blending. Based on the processing temperature requirements of the ICTE and the typical operating temperature range of wearable devices, it can be concluded that the stability of the ICTE is satisfactory for both thermoplastic processing and normal use scenarios.…”
Section: Resultsmentioning
confidence: 99%
“…For the ICTE and C-PEG, the first-stage weight loss above 100 °C is likely related to the volatilization of residual water and PC . Although the initial weight loss temperature of the ICTE was 100 °C, the weight loss rate (<0.5%) was almost negligible in plastic processing. , In this study, the preparation and molding of the ICTE were conducted at 92 °C, indicating that the ICTE remained highly stable during blending. Based on the processing temperature requirements of the ICTE and the typical operating temperature range of wearable devices, it can be concluded that the stability of the ICTE is satisfactory for both thermoplastic processing and normal use scenarios.…”
Section: Resultsmentioning
confidence: 99%
“…3c). 30,35,46–53 We also studied the mechanical properties of elastomers without IA, AA and DMA (as (P(AA/DMA), P(IA/DMA) and P(IA/AA), respectively). Comparing the three samples in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the preparation of ionic conductive elastomers with good electrical conductivity, light transmission, self-adhesion, high mechanical strength and high tensile properties remains challenging. In our previous work, 35 we obtained an ionic conductive elastomer with high transparency and strong self-adhesion through one-step photopolymerization of an AA/ChCl-type PDES with N , N -dimethylacrylamide (DMA), although this elastomer has high mechanical strength (9.27 MPa) and good tensile properties (1071%). However, compared with the high tensile strength reported in the literature, 36–38 its mechanical strength needs to be further improved.…”
Section: Introductionmentioning
confidence: 99%